2019
DOI: 10.1002/ajp.23078
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual and food characteristics on food retrieval and food sharing in captive Guinea baboons (Papio papio)

Abstract: Access to food is of major importance to the fitness and survival of every individual, particularly in group‐living animals, in which individual characteristics and food distribution can affect food intake. Additionally, several species of primates are known to share food under certain conditions. Such unresisted transfer of food from one individual to another appears to be adaptive, for instance as a tool to maintain and reinforce social bonds. In this study, we aimed to test how food retrieval and food shari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
5
2
0
Order By: Relevance
“…In a previous study comparing the Gibraltar group to other three wild groups of macaques with different dominance styles (i.e., Japanese macaques, long-tailed macaques, Macaca fascicularis, and moor macaques, M. maura), for instance, we found that more central individuals had a higher probability of retrieving food in all species (Amici et al, 2020). Such link between sociality and access to food has also been found in other species (Guinea baboons, Papio papio: Dell' Anna et al, 2019) and suggests that social integration, by affecting individuals' ability to access resources, might have a strong direct impact on their fitness and well-being (Dell' Anna et al, 2019;Amici et al, 2020). These results are also in line with previous studies showing a link between sociality and fitness in both human (Smith and Christakis, 2008;Holt-Lunstad et al, 2010) and non-human primates (e.g., baboons: Silk et al, 2003Silk et al, , 2009Silk et al, , 2010Archie et al, 2014; Assamese macaques, Macaca assamensis: Schülke et al, 2010), including Barbary macaques (McFarland and Majolo, 2013;Lehmann et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study comparing the Gibraltar group to other three wild groups of macaques with different dominance styles (i.e., Japanese macaques, long-tailed macaques, Macaca fascicularis, and moor macaques, M. maura), for instance, we found that more central individuals had a higher probability of retrieving food in all species (Amici et al, 2020). Such link between sociality and access to food has also been found in other species (Guinea baboons, Papio papio: Dell' Anna et al, 2019) and suggests that social integration, by affecting individuals' ability to access resources, might have a strong direct impact on their fitness and well-being (Dell' Anna et al, 2019;Amici et al, 2020). These results are also in line with previous studies showing a link between sociality and fitness in both human (Smith and Christakis, 2008;Holt-Lunstad et al, 2010) and non-human primates (e.g., baboons: Silk et al, 2003Silk et al, , 2009Silk et al, , 2010Archie et al, 2014; Assamese macaques, Macaca assamensis: Schülke et al, 2010), including Barbary macaques (McFarland and Majolo, 2013;Lehmann et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Less central individuals had a lower latency to approach the novel side (as compared to the familiar one), suggesting that individuals being less integrated in their social group are also less neophobic, or perhaps more likely to overcome neophobia to increase their food intake. These results are in line with recent studies on primates showing that less central individuals have a lower probability of retrieving food (Amici et al 2020 ; Dell'Anna et al 2020 ) and are also more likely to overcome neophobia when access to food is uneven across group members (Amici et al 2020 ). Across species, less central individuals may more often have to rely on novel food sources to get a share of resources so that lower neophobia might be selected for.…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, it is possible that different personalities may have complementary functions at the group level, with more neophobic individuals contributing to the maintenance of group cohesion (thus also being more central) and less neophobic individuals contributing to the exploration of novel resources and the spread of the group (see Michelena et al 2009 ). In both cases, social integration in the group appears to have a complex encompassing effect on individual fitness, in line with other studies in human (Smith and Christakis 2008 ; Holt-Lunstad et al 2010 ) and nonhuman primates (Silk et al 2003 , 2009 , 2010 ; Schülke et al 2010 ; Archie et al 2014 ; Dell'Anna et al 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of our study confirm that, beyond dominance rank, other individual characteristics like social integration (measured as Eigenvector centrality in the social network) may have a crucial effect on individuals' ability to access resources. Although the role of social integration in access to food has rarely been investigated, these results are in line with a recent study on captive Guinea baboons (Papio papio 22 ) and support a clear link between social integration and fitness in both human 77,78 and non-human primates [50][51][52]54,55 .…”
Section: Discussionsupporting
confidence: 89%